ISLAMIC BANKING AND SUKUK AS ALTERNATIVE FINANCING SOURCES IN DEVELOPMENT - Affandi, Faisal; Harahap, Isnaini; M. Nawawi, Zuhrinal (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
Islamic banking and sukuk, in the context of modern economic development, serve not only as financial instruments but also as vehicles to propagate ethical values and justice in society. In responding to the demands of the times, Islamic banking and sukuk have evolved into key players shaping the direction of global financial and economic development. The aim of this research is to analyze the crucial role of Islamic banking and sukuk as alternative financing sources in development. This research method utilizes literature review and employs descriptive analysis. The results show that Islamic banking in Indonesia plays a crucial role in supporting development financing, providing alternatives for individuals and the government interested in engaging in economic activities in line with Sharia principles. The financing provided by Islamic banking includes various types, such as murabahah financing (sale and purchase with fixed profit), mudarabah (investment cooperation), and musyarakah (ownership cooperation). Sukuk, as a Sharia financing instrument, has become the primary choice of the Indonesian government to support development projects. By issuing sukuk, the government can access substantial funds from the financial market, both at the national and international levels. Sukuk in Indonesia is often used to finance large-scale infrastructure projects such as toll roads, ports, and energy projects.